2009
DOI: 10.1007/s11934-009-0074-z
|View full text |Cite
|
Sign up to set email alerts
|

Penile shortening after radical prostatectomy and Peyronie’s surgery

Abstract: Penile shortening following radical prostatectomy and straightening procedures for Peyronie's disease can be a devastating and unwelcome side effect of these operations. The majority of men undergoing radical prostatectomy for prostate cancer have a measured loss of penile length, which also can occur in men with Peyronie's disease and may be exacerbated by surgery. Recent studies have investigated the mechanisms resulting in penile shortening, and various treatments have emerged to prevent and treat postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…This is underlined by the results of the studies mentioned above, although the precise mechanism is unknown [34–37]. With regard to sympathetic overactivity, it has been proposed that the sympathetic nerves recover faster than other nerves, thus causing chronic contractions of the cavernous smooth muscle tissue [41]. However, no studies have confirmed this hypothesis.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…This is underlined by the results of the studies mentioned above, although the precise mechanism is unknown [34–37]. With regard to sympathetic overactivity, it has been proposed that the sympathetic nerves recover faster than other nerves, thus causing chronic contractions of the cavernous smooth muscle tissue [41]. However, no studies have confirmed this hypothesis.…”
Section: Resultssupporting
confidence: 55%
“…The pathophysiology of PS is largely unknown, and trials in human subjects are scarce. A number of mechanisms have been proposed and count anatomic alterations, neural damage, sympathetic nervous system overactivity, and histological alterations [41].…”
Section: Resultsmentioning
confidence: 99%
“…Indentation, hinging, or buckling of the erect penis when axial forces are applied, as well as shortening, should also be determined. Shortening appears to occur in 70% of patients presenting with PD, which can be less than a centimeter to as much as 10 cm [10]. Although curvature is considered the most common presenting complaint to the physician, penile shortening tends to be one of the most devastating complications to the patient.…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…Sexual dysfunction three years post-treatment is common across all modalities (nerve sparing RP 68%, non-nerve sparing RP 87%, external RT 68%, brachytherapy 36%, ADT 98%) [4]. Treatment-induced changes in sexual function include erectile dysfunction (ED), absent or diminished ejaculate, changed orgasmic sensation, urine loss during arousal or orgasm (climacturia), decreased libido and penile shortening [5-7]. In addition to these physical side-effects, men also report impaired body image and self-esteem [4,8,9].…”
Section: Introductionmentioning
confidence: 99%